A Multidimensional Model for Integrating Qur’anic Verses in Arabic Language Learning - Rosikh, Fahrur; Ma’arif, A. Samsul; Ulfa, Maria (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Arabic holds a central place in the Islamic intellectual tradition as the language of the Qur’an. Therefore, Arabic instruction in Islamic higher education is expected not only to develop linguistic competence but also to integrate Qur’anic values into the learning process. However, in practice, much of the existing literature and instructional approaches continue to focus primarily on structural and linguistic aspects. Comprehensive models that systematically connect language skills with spiritual and ethical dimensions remain limited. This gap highlights the lack of a multidimensional framework that meaningfully integrates these elements. This study aims to examine the model and implementation of integrating Qur’anic verses into Arabic language learning at Universitas Sunan Drajat Lamongan. Using a qualitative case study approach, data were collected through classroom observations, in-depth interviews with lecturers and students, and document analysis. The data were then analyzed through an interactive process involving data reduction, data display, and conclusion drawing. The findings reveal a novel five-dimensional integrative model consisting of linguistic, contextual, thematic, value-based, and pedagogical integration. In this model, the Qur’an functions not only as a linguistic resource but also as an epistemological and pedagogical foundation. The implementation of this model follows a structured set of stages: introduction, language exploration, communicative practice, value reflection, and evaluation. This approach contributes to the simultaneous development of linguistic competence, communicative ability, and the internalization of Qur'anic values.